2010
DOI: 10.1080/09540100903443725
|View full text |Cite
|
Sign up to set email alerts
|

Wheat and gluten in South African food products

Abstract: Individuals with allergies and intolerances to grain products rely on accurate food labelling to prevent potentially life-threatening reactions. The aim of this study was to evaluate a number of South African food products for gluten and wheat to ascertain whether these products may pose a risk to celiac and/or wheat allergic individuals. Twenty-five products were analysed, including spelt products, flours of buckwheat, barley, rye, rice, millet, maize, semolina, triticale, oats, porridges, rice-and maize-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The use of Proteinase K less than 30μl did not feasible for production of high quantity and purity of DNA while in present study we just used 7-20μl of Proteinase K which produced high quantity and purified DNA [26]. Isolated DNA with range of 1.7-2.0 at absorbance A 260 /A 280 is considered pure [27]. Present study showed that the GeneJET Genomic DNA Purification Kit has short incubation time and economic, as compared to analysed six traditional methods.…”
Section: Resultsmentioning
confidence: 99%
“…The use of Proteinase K less than 30μl did not feasible for production of high quantity and purity of DNA while in present study we just used 7-20μl of Proteinase K which produced high quantity and purified DNA [26]. Isolated DNA with range of 1.7-2.0 at absorbance A 260 /A 280 is considered pure [27]. Present study showed that the GeneJET Genomic DNA Purification Kit has short incubation time and economic, as compared to analysed six traditional methods.…”
Section: Resultsmentioning
confidence: 99%
“…sea bass. Another example is the severely overexploited red stumpnose "Chrysoblephus gibbiceps" that was sold as the white stumpnose "Rhabdosargus globiceps" [18] . In addition, in Canada, the Japanese amberjack "Seriola quinqueradiata" was sold as the yellowfin tuna "Thunnus albacares", which is categorized as near-threatened species in the IUCN red list of species [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies have used R5 Skerritt (38)(39)(40) or G12 (41) . Western blot has generally been used as a complementary method to ELISA (42,43) , and in parallel, some of the studies have used a PCR method (43)(44)(45)(46)(47)(48) (Tables 1, 2 and 3).…”
Section: Methods Used To Estimate the Prevalence Of Gluten Contaminationmentioning
confidence: 99%